The Downregulated Lipo-Related Gene Expression Pattern in Keloid Indicates Fat Graft Is a Potential Clinical Option for Keloid - Li, Xueqing; Zhu, Zhaowei; Xu, Yangbin; Xu, Shuqia (Frontiers in Medicine, 2022)
Background: Keloids are a common complication of wounds, often manifesting with continuous hyperplasia and aggressive growth. Keloids also have a high recurrence rate and are largely resistant to treatment, making them clinically incurable, highlighting the need to translate basic research into clinical practice. Materials and Methods: We used GSE158395 and GSE92566 as discovery datasets to identify specific enriched hub genes and lncRNAs associated with keloid development and progression. This data was then used to identify the competing endogenous RNAs (ceRNAs) in these pathways by using a bidirectional selection method. Then, all hub genes and lncRNAs in ceRNAs were validated using GSE90051, GSE178562, and GSE175866, which describe the transcriptional profiles of keloid tissues, fibroblasts from pathological scars, and keloid fibroblast subpopulations, respectively. qPCR was performed using keloid tissue. Results: Both fat-associated biological processes and fat cell differentiation were enriched in the downregulated gene set. Further evaluation revealed that all 11 hub genes were lipo-related, and most of these were differentially expressed in all three validation datasets. We then identified a clear ceRNA network within the data comprising six hub genes and four lncRNAs. Evaluations of the validation datasets confirmed that all six of these hub genes and two of the four lncRNAs were downregulated in keloid tissues; two hub genes and one lncRNA were downregulated in fibroblasts from pathological scars; and five hub genes and one lncRNA were significantly downregulated in mesenchymal subpopulation. Three genes had statistical difference and eight genes showed downregulated trend through qPCR of the keloid tissue. Conclusion: Our results suggest that keloid development relies on the downregulation of lipo-related genes and pre-adipocytes in diseased tissues and may be one of the key mechanisms underlying fat grafting-mediated treatment of pathological scarring.